DETECTION OF PREOVULATORY FOLLICLE SIZE AND EARLY PREGNANCY BY USING ULTRASONOGRAPHY IN THOROUGHBRED MARES DURING FOAL HEAT - ARBAL, R W; INGAWALE, M V; DESHMUKH, S G; HAJARE, S W (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to detect the preovulatory follicle diameter and early pregnancy detection using ultrasonography in Thoroughbred mares. The follicular growth were recorded from day 8 postpartum till ovulation daily by using ultrasound machine with 5-, 7.5 MHz transrectal probe in twelve normally foaled Thoroughbred mares. All mares which were detected with largest follicle size and a characteristic uterine pattern of edema (cart-wheel like appearance) were mated with stallion every second day. Ultrasonography was carried out for early pregnancy diagnosis from day 14th post mating. The mean diameter of preovulatory follicle was 40.9104.52 mm and early pregnancy was diagnosed in 100% mares on 14th day by detecting the embryonic vesicle with mean size of 10.2500.59 mm by transrectal ultrasonography.